From Clinic to Policy: Advancing Sustainable Dentistry through Public Health Systems: Sustainable Dentistry and Public Health - Sanjida Haque (Indonesian Journal of Health Research and Development, 2026)
Background: Dentistry generates significant biomedical waste, utilizes energy-intensive resources, and employs materials harmful to the environment, such as dental amalgam. The concept of dental sustainability is in line with international targets like the UN Sustainable Development Goals (SDGs) and the Minamata Convention on Mercury.Aims: This narrative policy review analyzes how dental associations and public health systems may lead policy, educate, advocate, and reform dentistry to make it more sustainable.Methods: The study was performed based on peer-reviewed sources, as well as international policy and professional guidelines. PubMed, Scopus, Google Scholar, WHO, FDI, ADA, NHS, and national regulatory bodies were target sources of evidence. A synthesis of literature on the effects of the environment, sustainability programs, waste management, amalgam phase-down, digital dentistry, and governance of health systems was performedResult: Worldwide efforts, including the FDI Sustainability in Dentistry Policy Statement (2021) and national strategies, including the NHS Net Zero Plan, show evidence of an ever-growing trend in favor of sustainability in the dental care sector. Nevertheless, lack of financial resources, poor awareness, poor management systems, and inconsistent implementation of policies hinder achievements. Clinical standards can be influenced by dental associations, and the wider change is enabled by the involvement of the regulation, reform of procurement, and development of the infrastructure by the public health systems.Conclusion: The integration of sustainability in dentistry requires a collaborative effort from both professional associations and public health systems. Improving policy, education, innovation, and regulation can ensure that dentistry contributes positively to both oral health and environmental protection.